2011
DOI: 10.1504/ijqi.2011.040428
|View full text |Cite
|
Sign up to set email alerts
|

Defect control analysis for improving quality and productivity: an innovative Six Sigma case study

Abstract: This research study proposes an innovative analysis for controlling the defects in aluminium die casting industry. In this analysis, casting process of a two-stroke engine oil pump body is concentrated. The component selected has often rejected due to blow hole defects. Six Sigma, the zero defect approach, is used in this study. Define measure, analyse, improve and control (DMAIC) problem solving methodology is applied for problem analysis. Taguchi's experimental design is used for process validation and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…These databases provide online delivery systems with full text access to thousands of high-quality articles and journals that cover a wide range of case studies of casting, chemical, textile, plastic, paper, steel manufacturing, auto, food processing, aerospace, electric and electronics industries. There are 112 research case studies taken for the critical review and analysis of measuring the success of Six Sigma in manufacturing industry (Thomas et al , 2016; Sahoo et al , 2007; Kuthe and Tharakan, 2009; Laureani and Antony, 2012; Singh and Khanduja, 2014; Chiarini, 2015; Andrew, 2009; Andrew and Barton, 2006; Andrew et al , 1994; Rivera and Marovich, 2001; Prashar, 2014a,b; Prashar, 2015; Singh et al , 2012; Bilgen and Sen, 2012; Cheng and Kuan, 2012; Hardeman and Goethals, 2011; Desai, 2012; Desai, 2008; Powell et al , 2017; Pranckevicius et al , 2008; Gijo et al , 2011; Gijo and Scaria, 2010; Gijo et al , 2014; Gijo et al , 2014; Lin and Wong, 2014; Amitrano and Lígia de Oliveira, 2014; Filardi et al , 2015; Wang and Chen, 2012; Radha Krishna and Dangayach, 2007; Nithyanandama and Pezhinkattilb, 2014; Maheshwar, 2012; Besseris, 2011; Barbosa et al , 2014; Sekhar and Mahanti, 2003; Hong, 2012; Nunes, 2015; Wu et al , 2011; Antony et al , 2012; Antony et al , 2016; Chen et al , 2014; Leu and Lee, 2016; Srinivasan et al , 2016; Srinivasan et al , 2014a, b; Chen et al , 2006; Srinivasan et al , 2014a, b; Gupta et al , 2014; Lee and Wei, 2010; Meng et al , 2011; Simanova, 2015; Kumar et al , 2006; Shanmugaraja et al , 2011; Kumar et al , 2007; Dora and Gellynck, 2015; Cabrita et al , 2015; Franchetti and Yanik, 2011; Franchetti and Pukhraj, 2013; Cournoyer et al , 2012; Zhang et al , 2014; Zhang et al , 2014; Shu et al , 2012; Kim et a...…”
Section: Research Methodology Adopted For Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These databases provide online delivery systems with full text access to thousands of high-quality articles and journals that cover a wide range of case studies of casting, chemical, textile, plastic, paper, steel manufacturing, auto, food processing, aerospace, electric and electronics industries. There are 112 research case studies taken for the critical review and analysis of measuring the success of Six Sigma in manufacturing industry (Thomas et al , 2016; Sahoo et al , 2007; Kuthe and Tharakan, 2009; Laureani and Antony, 2012; Singh and Khanduja, 2014; Chiarini, 2015; Andrew, 2009; Andrew and Barton, 2006; Andrew et al , 1994; Rivera and Marovich, 2001; Prashar, 2014a,b; Prashar, 2015; Singh et al , 2012; Bilgen and Sen, 2012; Cheng and Kuan, 2012; Hardeman and Goethals, 2011; Desai, 2012; Desai, 2008; Powell et al , 2017; Pranckevicius et al , 2008; Gijo et al , 2011; Gijo and Scaria, 2010; Gijo et al , 2014; Gijo et al , 2014; Lin and Wong, 2014; Amitrano and Lígia de Oliveira, 2014; Filardi et al , 2015; Wang and Chen, 2012; Radha Krishna and Dangayach, 2007; Nithyanandama and Pezhinkattilb, 2014; Maheshwar, 2012; Besseris, 2011; Barbosa et al , 2014; Sekhar and Mahanti, 2003; Hong, 2012; Nunes, 2015; Wu et al , 2011; Antony et al , 2012; Antony et al , 2016; Chen et al , 2014; Leu and Lee, 2016; Srinivasan et al , 2016; Srinivasan et al , 2014a, b; Chen et al , 2006; Srinivasan et al , 2014a, b; Gupta et al , 2014; Lee and Wei, 2010; Meng et al , 2011; Simanova, 2015; Kumar et al , 2006; Shanmugaraja et al , 2011; Kumar et al , 2007; Dora and Gellynck, 2015; Cabrita et al , 2015; Franchetti and Yanik, 2011; Franchetti and Pukhraj, 2013; Cournoyer et al , 2012; Zhang et al , 2014; Zhang et al , 2014; Shu et al , 2012; Kim et a...…”
Section: Research Methodology Adopted For Studymentioning
confidence: 99%
“…Six Sigma helps to improve productivity, quality of product and achieve customer delight for the auto sector. Kumaravadivel and Natarajan (2013), Singh et al (2016), Kumar et al (2006), Shanmugaraja et al (2011) and Kumar et al (2011) implemented Six Sigma methodology to reduce defects in the process. Srinivasan et al (2014a, b) reduced defects of paint line in shock absorber by using Six Sigma methodology.…”
Section: Classification Frameworkmentioning
confidence: 99%
“…According to a study by Shanmugaraja et al [10], it was found that in India, six sigma has been applied in small and medium enterprises (SMEs) by introducing the DMAIC process in the casting process to reduce the rejection rate that occurs. Desai and Prajapati [2] have implemented the six sigma DMAIC process in steel and plastic manufacturing industries, which face a high number of sorting problems.…”
Section: Experimental Designmentioning
confidence: 99%
“…In another case study of automobile ancillary SME located in south India, producing automobile aluminum components for various clienteles in India and abroad, Six Sigma was applied to casting process of a two-stroke engine oil pump body to reduce rejection rate mainly due to blow holes. With the application of DMAIC methodology rejection rate was reduced to 4.8 from 17.22 per cent (Shanmugaraja et al , 2011). Ghosh and Maiti (2014) implemented DMAIC approach in a large foundry located in western India to reduce large rejection rate in one of the critical products, grey iron cylinder head casting used in automobiles.…”
Section: Literature Reviewmentioning
confidence: 99%